The Study On Antioxidant And Anti-Inflammatory Effects Of Sodium Copper Chlorophyllin In Male Rats Receiving Indomethacin - Ibrahim H. Muslim; Nadheerah F. Neamah; Falah H. Shari (Academia Open, 2024)
Sodium copper chlorophyllin (SC-C) is widely used for its biological properties and color. This study evaluated SC-C's antioxidative and anti-inflammatory effects in male rats treated with indomethacin. Fifty rats were divided into five groups: control, indomethacin, rabeprazole, and two SC-C dosages (35 mg/kg and 70 mg/kg). Indomethacin reduced serum GPx levels, but rabeprazole and SC-C treatments restored them. MDA levels increased with indomethacin but normalized with other treatments. Indomethacin also lowered IL-10, IL-4, and TNF, which returned to normal in treated groups. Histopathology showed SC-C reversed liver damage from indomethacin. SC-C demonstrates strong antioxidant and anti-inflammatory activities, suggesting its potential as a therapeutic agent. Highlight: SC-C significantly restores serum GPx levels reduced by indomethacin. SC-C normalizes MDA, IL-10, IL-4, and TNF levels, countering oxidative stress. Histopathology shows SC-C reverses liver damage induced by indomethacin. Key wards: Sodium copper chlorophyllin, antioxidant, anti-inflammatory, indomethacin, oxidative stress